2014
DOI: 10.1126/science.1247190
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin-Mediated GABA Inhibition During Delivery Attenuates Autism Pathogenesis in Rodent Offspring

Abstract: We report that the oxytocin-mediated neuroprotective γ-aminobutyric acid (GABA) excitatory-inhibitory shift during delivery is abolished in the valproate and fragile X rodent models of autism. During delivery and subsequently, hippocampal neurons in these models have elevated intracellular chloride levels, increased excitatory GABA, enhanced glutamatergic activity, and elevated gamma oscillations. Maternal pretreatment with bumetanide restored in offspring control electrophysiological and behavioral phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
517
2
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 529 publications
(559 citation statements)
references
References 28 publications
31
517
2
5
Order By: Relevance
“…In line with this hypothesis Tyzio et al . (2014) and He et al . (2014) demonstrated that in different mouse models of ASD, neuronal Cl − homeostasis and GABA polarity are fundamentally altered, such that neurons retain high [Cl − ] i and depolarizing E GABA .…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 97%
See 2 more Smart Citations
“…In line with this hypothesis Tyzio et al . (2014) and He et al . (2014) demonstrated that in different mouse models of ASD, neuronal Cl − homeostasis and GABA polarity are fundamentally altered, such that neurons retain high [Cl − ] i and depolarizing E GABA .…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 97%
“…Moreover the authors established that the maternal hormone OXT is a critical regulator of the GABA polarity shift (Tyzio et al . 2006, 2014). OXT treatment of ASD animals reversed several cellular, physiological and behavioural phenotypes of ASD, and this phenotypic rescue could be blocked with the OXT receptor (OXTR) antagonist SSR126768A.…”
Section: Gpcr Modulation: a Brief Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…by guest on April 20, 2019 www.aappublications.org/news Downloaded from the deleterious effects of enhanced activity of GABA signaling, 27 in addition to the current evidence of changes in brain connectivity after OXT administration in infants <6 months old, suggest a continuum in the role of OXT from birth to early postnatal life.…”
Section: Figurementioning
confidence: 98%
“…Currently, bumetanide is under study in a phase I/II clinical trial as a single add-on therapy to existing phenobarbital treatment for neonatal seizures in infants 33-44 wks of age at dosages of 0.1-0.3 mg/kg (clinicaltrials.gov, NCT00830531). Interestingly, autistic behaviors, one of the developmental outcomes associated with PVL in survivors of preterm birth, have been shown to decrease in a small cohort of human subjects following bumetanide treatment (16,17); bumetanide treatment has also been shown to restore abberant behavior and brain oscillations in animal models of autism when given prenatally (18).…”
Section: Bumetanide Protection In Rodent Pvlmentioning
confidence: 99%